Neuromuscular Properties of the Human Wrist Flexors as a Function of the Wrist Joint Angle - Behrens, Martin; Husmann, Florian; Mau-Moeller, Anett; Schlegel, Jenny; Reuter, Eva-Maria; Zschorlich, Volker R. (Frontiers in Bioengineering and Biotechnology, 2019)
The joint angle dependence of voluntary activation and twitch properties has been investigated for several human skeletal muscles. However, although they play a key role for hand function and possess a unique neural control compared to muscles surrounding other joint complexes, little is known about the wrist flexors innervated by the median nerve. Therefore, isometric voluntary and electrically evoked contractions of the wrist flexors were analyzed at three wrist joint angles (extension: −30°, neutral: 0°, flexion: 30°) to quantify the joint angle dependence of (i) voluntary activation (assessed via peripheral nerve stimulation and electromyography [EMG]), (ii) unpotentiated twitch torques, and (iii) potentiated twitch torques. Maximum voluntary torque was lower in extension compared to neutral and flexion. Although voluntary activation was generally high, data indicate that voluntary activation of the wrist flexors innervated by the median nerve was lower and the antagonist·agonist−1 EMG ratio was higher with the wrist joint in flexion compared to extension. Peak twitch torque, rate of twitch torque development, and twitch half-relaxation time increased, whereas electromechanical delay decreased from flexion to extension for the unpotentiated twitch torques. Activity-induced potentiation partly abolished these differences and was higher in short than long wrist flexors. Different angle-dependent excitatory and inhibitory inputs to spinal and supraspinal centers might be responsible for the altered activation of the investigated wrist muscles. Potential mechanisms were discussed and might have operated conjointly to increase stiffness of the flexed wrist joint. Differences in twitch torque properties were probably related to angle-dependent alterations in series elastic properties, actin-myosin interaction, Ca2+ sensitivity, and phosphorylation of myosin regulatory light chains. The results of the present study provide valuable information about the contribution of neural and muscular properties to changes in strength capabilities of the wrist flexors at different wrist joint angles. These data could help to understand normal wrist function, which is a first step in determining mechanisms underlying musculoskeletal disorders and in giving recommendations for the restoration of musculoskeletal function after traumatic or overuse injuries.